2023
DOI: 10.1177/23780231231181859
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and Inequality in the Professoriate: How and Why First-Generation and Working-Class Backgrounds Matter

Abstract: Social science research has long recognized the relevance of socioeconomic background for mobility and inequality. In this article we interrogate how and why working-class and first-generation backgrounds are especially meaningful and take as our case in point the professoriate and the discipline of sociology, – i.e., a field that intellectually prioritizes attention to group inequality and that arguably offers a conservative empirical test compared to other academic fields. Our analyses, which draw on unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 117 publications
0
7
0
Order By: Relevance
“…Such analysis would garner longer term insights into the meaning of FG status, especially as it shifts across time in the academy, and the constraints and affordances of broader social and organizational environments as they shape FGF experience, longevity, and success. For example, although this systematic review found that FGF experience cultural discord in the academy, this dissonance and its social and psychological consequences are not explored in depth (Roscigno et al, 2023); neither are the factors that contribute to differences in how FGF experience and navigate this cultural divide. Research could uncover the diverse, and potentially divergent, experiences among FGF, with insight into reveal how social and organizational contexts may differentially marginalize members of this group and how broader social and institutional contexts situate the realities of FGF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such analysis would garner longer term insights into the meaning of FG status, especially as it shifts across time in the academy, and the constraints and affordances of broader social and organizational environments as they shape FGF experience, longevity, and success. For example, although this systematic review found that FGF experience cultural discord in the academy, this dissonance and its social and psychological consequences are not explored in depth (Roscigno et al, 2023); neither are the factors that contribute to differences in how FGF experience and navigate this cultural divide. Research could uncover the diverse, and potentially divergent, experiences among FGF, with insight into reveal how social and organizational contexts may differentially marginalize members of this group and how broader social and institutional contexts situate the realities of FGF.…”
Section: Discussionmentioning
confidence: 99%
“…“First-generation” is categorized variously based on a range of overlapping interpretations of parents’ educational and socioeconomic background, including the highest degree completed (e.g., high school diploma) or college enrollment and/or experience without acquiring a bachelor’s degree (Choy, 2001; Jehangir, 2010; J. J. Lee et al, 2004; Roscigno et al, 2023). To cast a wide net of inclusion, this article employs the original and most expansive definition of FG: a person without at least one parent or guardian who has completed a bachelor’s degree (Nguyen & Nguyen, 2018).…”
Section: Defining “First-generation” Intersectionallymentioning
confidence: 99%
“…Further attention to graduate enrollment and graduate student populations is warranted, but recent research on undergraduates (Aries 2008;Hurst 2019;Jack 2019;Lee 2016;Stuber 2011;Wilbur and Roscigno 2016) and faculty of working-class and first-generation backgrounds (Arner 2021;Haney 2015;Roscigno et al 2023) is informative to our focus, particularly when it comes to graduate school barriers. A few analyses indeed point to patterns of disadvantage and vulnerability that persist into graduate education (e.g., Smith, Mao, and Deshpande 2016).…”
Section: Graduate School Access Enrollment and Potential Pipeline Ine...mentioning
confidence: 99%
“…Inequalities in cultural capital, truncated social networks, family responsibilities, and identity consequences (e.g., sense of isolation and imposter syndrome) are common themes among first-generation and working-class students who eventually make it to graduate school (Warnock 2016). In contrast to individuals who received PhDs in the 1960s and 1970s, who may have struggled with feelings of psychological dislocation but who otherwise achieved all the hallmarks of academic success (e.g., attendance at top programs, publications, awards), accounts from more newly minted academics point to a stronger link between social origins and mobility into and through graduate school, with important long-term consequences (e.g., greater job-specific precarity, financial stress, and debt; Roscigno et al 2023). This emerging literature points to potential pipeline inequalities and, specifically, the following expectation:…”
Section: Graduate School Access Enrollment and Potential Pipeline Ine...mentioning
confidence: 99%
See 1 more Smart Citation